A computationally efficient model to predict the uniaxial tensile loading response for dry woven fabrics. (1st October 2018) - Yang, Yabin; Zeng, Pan
Abstract: Woven structure is an essential component widely used in composite materials, bio-materials and mechanical metamaterials. The mechanical response of the dry woven fabric, which is widely used as reinforcement in composite materials is studied in the present paper. Typically, for the dry woven fabric, the warp and weft yarns are weaved with each other. Each warp or weft yarn also consists of large amounts of small filaments. Because of this multiscale nature, a model that can predict the material response as a function of the underlying structure is important for the design of the dry woven fabric. Hence, a computationally efficient model to simulate the uniaxial tensile loading response for dry woven fabrics is proposed. The proposed model is able to predict the macroscopic loading-deformation response, the effective in-plane Poisson's effect and the deformation of the thickness by taking into account the influence of the filaments, the weaving pattern and the surface contact at the crossover of the yarns. The accuracy of the model is validated by a digital image correlation (DIC) experiment. For the weaved yarns, complex yarn geometries can be easily modelled and different yarn curve assumptions can be conveniently incorporated in the proposed model. The high computational efficiency of the model makes it potentially helpful for designing woven materials with high mechanical performance.